Astudy of some aspects of reproductive Performance in rabbits treated with Hydrocortisone - Al- Ar rak, J. K. (The Iraqi Journal of Veterinary Medicine, 2001)
This experiment was carried out to study the changes in some of the structural – functional and biochemical aspects that are related to reproductive performance as a result of using glncocorticoid - hydrocortisone. Twelve adult male rabbit were divided into two equal groups : control and treatment. During pretreatment period ( Five days) blood samples were collected from all animals on every other days . During the treatment period (14) days each animal of the treatment group was injected daily , intramuscularly with hydrocortisone . Rabbit of the control group were injected with the same dose of normal physiological saline. Blood samples were collected as described above until (48) hours after last injection . All animals were scarified and samples from testicular tissue were taken to study structural – functional aspect. Statistical analysis showed significant (P < 0.05) decrease in plasma testosterone of hydrocortisone treated rabbits, plasma levels of ICSH of both treatment and control groups of rabbits were parallel to each other (P< 0.05).